2009
DOI: 10.1016/j.jeem.2009.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The case for international emission trade in the absence of cooperative climate policy

Abstract: We evaluate the ecacy of international trade in carbon emission permits when countries are guided strictly by their national self-interest. To do so, we construct a calibrated general equilibrium model that jointly describes the world economy and the strategic incentives that guide the design of national abatement policies. Countries' decisions about their participation in a trading system and about their initial permit endowment are made noncooperatively; so a priori it is not clear that permit trade will ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 24 publications
4
108
0
1
Order By: Relevance
“…the United Nations Framework Convention on Climate Change, Kyoto Protocol, the Bali roadmap etc. However, as most countries are guided by their national self-interest to participate in global emission reduction agreements, the hope for cooperative efforts to reduce global emission is very little (Carbone et al, 2009). It is because the benefits of emission reduction are worldwide while the costs normally pertain to the country that makes efforts for emission reductions, no individual country would voluntary adopt emission abatement policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…the United Nations Framework Convention on Climate Change, Kyoto Protocol, the Bali roadmap etc. However, as most countries are guided by their national self-interest to participate in global emission reduction agreements, the hope for cooperative efforts to reduce global emission is very little (Carbone et al, 2009). It is because the benefits of emission reduction are worldwide while the costs normally pertain to the country that makes efforts for emission reductions, no individual country would voluntary adopt emission abatement policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reflecting recent discussions of the linkage of permit markets, this paper also examines the welfare implications of the permit market linkage that allows free international trade of those permits, no matter where they were originally issued. (The discussions can be found in Helm [8], Copeland and Taylor [9], Carbone, Helm, and Rutherford [10], Flanchsland, Marschinski, and Edenhofer [11], Ranson and Stavins [12], and Doda and Taschini [13]. )…”
Section: Introductionmentioning
confidence: 99%
“…found that stable coalitions might emerge if the environmental benefits are sufficiently high or if a proper transfer scheme is introduced. Carbone et al (2009) established that emission trade can be effective even if countries are guided by their national self-interest.…”
Section: Open Partial Agreement and Relation To The Literaturementioning
confidence: 99%